2006
DOI: 10.1007/s11284-006-0314-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–nitrogen stoichiometry in the tritrophic food chain willow, leaf beetle, and predatory ladybird beetle

Abstract: Although plant quality can indirectly increase the performance of the third trophic level by bottom-up cascading effects, the mechanisms of this indirect effect are still unclear. In this study the carbon-nitrogen stoichiometry in a tri-trophic system consisting of the willow, a leaf beetle, and a predatory ladybird beetle were examined to determine the mechanisms of the bottomup cascading effect. The bottom-up cascade is initiated by increasing leaf nitrogen, because of artificial cutting of willow trees. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…At the same time, this has also been shown for terrestrial systems, e.g. for carnivorous beetles by Kagata and Ohgushi (2007) in an experimental three-trophic-level food chain setup, and in a broader sense by Denno and Fagan (2003) who showed that even minor differences, usually found between predator and prey N stoichiometry, shape omnivory, but information on this specific field of research is still very limited.…”
Section: Introductionmentioning
confidence: 69%
“…At the same time, this has also been shown for terrestrial systems, e.g. for carnivorous beetles by Kagata and Ohgushi (2007) in an experimental three-trophic-level food chain setup, and in a broader sense by Denno and Fagan (2003) who showed that even minor differences, usually found between predator and prey N stoichiometry, shape omnivory, but information on this specific field of research is still very limited.…”
Section: Introductionmentioning
confidence: 69%
“…The relative growth rate of the chrysomelid increased when feeding on the nitrogen rich leaves, but nitrogen level did not increase in the body of the leaf beetle. Thus it is not clear why the relative growth rate also increased in the coccinellid larvae preying on the chrysomelid larvae feeding on N -rich leaves (Kagata & Ohgushi 2007 ; Elevated air CO 2 concentration signifi cantly increased tannin and gossypol content and decreased N content in cotton. The survival of Aphis gossypii increased with higher CO 2 concentrations while their fatty acid content decreased.…”
Section: Food Relationships 197mentioning
confidence: 99%
“…28 Qualitative traits of leaves, chrysomelids ( P lagiodera versicolora ) and ladybirds ( A iolocaria hexaspilota ) on cut and uncut willows (modifi ed afterKagata & Ohgushi 2007 ) .…”
mentioning
confidence: 99%
“…Specifically, carnivores that consumed herbivorous zooplankton raised on nutrient-replete phytoplankton grew more rapidly (thus, FCE was higher) than carnivores that consumed zooplankton fed nutrient-limited phytoplankton (Malzahn et al, 2007;Dickman et al, 2008;Schoo et al, 2010;Rowland et al, 2015). In a terrestrial system, Kagata & Ohgushi (2007) found that the growth rate of predatory ladybird beetles increased when fed herbivorous beetles raised on willow leaves with a low C:N, even though the C:N of the leaf beetles was not significantly different between treatments; this suggests that producer stoichiometry may affect traits of herbivores, other than stoichiometry, in ways that impact herbivore quality as food for higher trophic levels. However, such carry-over effects are not universally observed in experimental 3 trophic-level food chains (Boersma et al, 2008;Malzahn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%